An Employee Sharing Model for the Tourism and Hospitality Industry - Efrén De la Mora Velasco; Arthur Huang; Adam Haney (Tourism and Hospitality, 2021)
Fast technological developments have transformed the tourism and hospitality services and the labor market. The outbreak of the COVID-19 pandemic exposed the vulnerability of the tourism and hospitality workforce. There is insufficient prior work about creating better work conditions and greater career opportunities for hospitality and tourism professionals in the swiftly changing labor market. To this end, this article analyzes the historical employee–employer relationships in the tourism and hospitality industry. It presents a new employee-sharing model framework for enhancing resilience and flexibility for hospitality and tourism enterprises and workers.